Ninth Five Year Plan (1997-2002) and Annual Plan 1997-98 Volume-II Government of Manipur - Planning Commission (Planning Commission, 1997)
Abstract, Ninth Plan (1997-2002) and Annual Plan ( 1997-98) Outlays GN Statement Eighth Plan Expenditure Outlays for Ninth Plan (1997-2002) and Annual Plan (1997-98)Eighth Plan Physical Targets and achievements Ninth Plan (1997-2002) and Annual Plan. (1997-98) proposed Physical Target Proposals for spill-over and on-going Programmes /projects Completed Schemes as on 31.3,96, Liability schemes, Critical On-going Schemes Proposals for Maximising benefits of completed Programmes/Projects Proposals for Programmes/Projects New Schemes for Ninth Plan Summary Statement - Proposals for Programmes/Projects Externally Hided Projects.
Government of Manipur, Planning Department